2016
DOI: 10.1007/978-3-319-41769-1_5
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality for Early Education: A Study

Abstract: Abstract. This paper investigates the use of Virtual Reality (VR) as a tool for cultural heritage learning, using St Andrews Cathedral as the subject matter. As part of a module focused on local history, first year secondary school pupils in a school in the town of St Andrews took part in virtual tours of the Cathedral as it stood in the 14 th Century using the Samsung Gear VR, Google Cardboard, Oculus Rift, computer screen and Xbox controller, and answered questions aimed to elicit their experiences with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…Numerous studies on the application of virtualisation in educational environments have shown that it is not only effective in terms of teaching, but that this system stimulates interest in the subject, allowing students to develop new ideas or reformulate old ones (e.g. Christou, 2010;Elmqaddem, 2019;Fabola et al, 2016;Kavanagh et al, 2017). In the same way, the education system has been affected by the global pandemic, demonstrating that e-learning is also possible, and that projects such as the one presented here have a place in schools.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies on the application of virtualisation in educational environments have shown that it is not only effective in terms of teaching, but that this system stimulates interest in the subject, allowing students to develop new ideas or reformulate old ones (e.g. Christou, 2010;Elmqaddem, 2019;Fabola et al, 2016;Kavanagh et al, 2017). In the same way, the education system has been affected by the global pandemic, demonstrating that e-learning is also possible, and that projects such as the one presented here have a place in schools.…”
Section: Discussionmentioning
confidence: 99%
“…Fabola et al [27] investigated the use of virtual reality (VR) as a tool for learning about heritage, specifically St Andrews Cathedral. First year pupils from a secondary school in the city of St Andrews took part in virtual tours of the Cathedral as it was in the 14th century using Samsung Gear VR, Google Cardboard, Oculus Rift, computer screens and Xbox controllers and then answered questions about their experiences with the various systems.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, it has been seen that VR technologies are directly related to the suitability of image quality which is considered as the primary determinant in assessing effectiveness. For this reason, it is considered that the content to be used should be vivid with high resolution, which affects the users' preferences (Gome et al 2012& Fabola, Miller, 2016. It has also been pointed out that the visual quality of virtual VR technologies could be lower than the actual conditions, which would cause some problems that the users would deal with.…”
Section: Factors Limiting the Use Of Virtual Reality Technologymentioning
confidence: 99%